Constraints faced in the Adoption of Technologies by Chawki Rearing Centre Entrepreneurs - Basavaiah; Kallimani, Chandrashekar Shivappa (Journal of Extension Education, 2021)
Chawki Rearing Centres (CRCs) act as backbone of silkworm rearing activity. The study was conducted in 100 CRCs of six traditional sericultural districts of Karnataka with the objective of understanding the constraints faced by CRC entrepreneurs in adoption of recommended technologies. Through pilot survey, 30 constraints were identified and they were ranked based on Garrett score. While shortage of farm laborers, scarcity of irrigation water, lack of technical guidance in pest and disease management, difficulty in harvesting leaf and shootlet alternatively and high labor wages were the major constraints in adoption of mulberry leaf production technologies, inadequate rearing space, scarcity of skilled workers, lack of space for supporting activities, lack of technical guidance to diagnose diseases and high wages of skilled workers were the major constraints in adoption of silkworm rearing technologies. Measures to be taken to overcome these constraints are suggested.